PENGARUH PENGGUNAAN METODE BERCERITA DALAM BIMBINGAN DAN KONSELING TERHADAP MOTIVASI BELAJAR SISWA SMP ISLAM INTEGRAL LUQMAN AL HAKIM BATAM - afrizawati; M. Sidik; Afriyani (LP2M-Institut Agama Islam Abdullah Said Batam, 2021)
This research was motivated by the lack of enthusiasm of students in studying the material, rarely going to school, rarely or not completing assignments, not being creative, and even decreasing the quality of learning outcomes so that it has an impact on learning outcomes. Therefore, one of the ways to increase student learning motivation was chosen, with counseling guidance that is able to provide services that can motivate student learning. Based on Abraham Maslow's theory, this theory is carried out by meeting the needs of students, in order to achieve maximum and best learning outcomes. The results of the study showed that the planning of the guidance program had gone through a series of stages according to the theory. Student motivation experienced a significant change in each cycle, starting from the first cycle which showed the child's lack of enthusiasm, this can be seen from the increasing cognitive, affective and psychomotor aspects, lack of group cooperation to the inferior attitude of children who have less achievement gradually. changed in the third cycle.